Investigation of Archived Formalin-Fixed Paraffin-Embedded Pancreatic Tissue with Whole-Genome Gene Expression Microarray. (26th December 2011) - Michelsen, Nete V.; Brusgaard, Klaus; Tan, Qihua; Thomassen, Mads; Hussain, Khalid; Christesen, Henrik T.
Abstract : The use of formalin-fixed, paraffin-embedded (FFPE) tissue overcomes the most prominent issues related to research on relatively rare diseases: limited sample size, availability of control tissue, and time frame. The use of FFPE pancreatic tissue in GEM may be especially challenging due to its very high amounts of ribonucleases compared to other tissues/organs. In choosing pancreatic tissue, we therefore indirectly address the applicability of other FFPE tissues to gene expression microarray (GEM). GEM was performed on archived, routinely fixed, FFPE pancreatic tissue from patients with congenital hyperinsulinism (CHI), insulinoma, and deceased age-appropriate neonates, using whole-genome arrays. Although ribonuclease-rich, we obtained biologically relevant and disease-specific, significant genes; cancer-related genes; genes involved in (a) the regulation of insulin secretion and synthesis, (b) amino acid metabolism, and (c) calcium ion homeostasis. These results should encourage future research and GEM studies on FFPE tissue from the invaluable biobanks available at the departments of pathology worldwide.